The Influence of Utilization of Information Technology and Human Resources Capability on the Performance of Administrative Employees - Syafria Syafria; Supratman Supratman (International Journal of Management, Innovation, and Education, 2025)
This research was conducted at SMAN 1 Tilatang Kamang, which is located on Jalan Raya Pekan Kamis, Tilatang Kamang District, Agam Regency. This research is motivated by the initial observations that the author met in the field, there are several problems in the use of information technology used, especially the use of computers, the internet, and printer machines. There are only 10 TU employees, only 2 can operate a computer, and even then, it's just that. If fast electronic data is needed, they find it difficult to make it so they are often assisted by honorary personnel. This study aims to determine the effect of the use of information technology and human resource capabilities on the performance of Administrative Officers (TU) of SMAN 1 Tilatang Kamang. In connection with the research objectives above, a hypothesis is made that "it is suspected that the use of technology and human resource capabilities has a significant partial and simultaneous effect on employee performance". To conduct the discussion and research, the authors use primary data directly obtained from the object of research through a list of structured statements or questionnaires that have been answered by employees, and the population of this research is TU employees of SMAN 1 Tilatang Kamang, totaling 10 people using the Census method (Total Sampling). ). Data processing using SPSS 15.0 assistance method. The data analysis method used in this research is the Instrument Test, namely the Validity Test and Reliability Test, as well as Variable Descriptive Analysis. The analytical tool used is Multiple Linear Regression Analysis.